1979
DOI: 10.1002/1097-0142(197910)44:4<1465::aid-cncr2820440441>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Localized primary tumors of the pleura. An analysis of 40 cases

Abstract: A study of 40 localized primary tumors of the pleura in the files of the Canadian Tumour Reference Centre revealed a considerable diversity in their histologic structure. Collagenized, hemangiopericytoma-like and cellular areas were the main forms of growth pattern, with half of the tumors showing a mixture of two or more of these elements. Inclusions of non-neoplastic bronchioloalveolar epithelium were frequently seen in areas of tumor adjacent to lung substance but in only one tumor was there a neoplastic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
72
0
9

Year Published

1980
1980
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(82 citation statements)
references
References 19 publications
1
72
0
9
Order By: Relevance
“…SFTs with local or distant recurrences are often larger than 10 cm on presentation (3,6). Benign SFT of the pleura has a high cure rate and an 8% local recurrence rate that is usually amenable to curative re-excision, often with chest wall resection because of the propensity for local recurrence (16).…”
Section: Discussionsupporting
confidence: 83%
“…SFTs with local or distant recurrences are often larger than 10 cm on presentation (3,6). Benign SFT of the pleura has a high cure rate and an 8% local recurrence rate that is usually amenable to curative re-excision, often with chest wall resection because of the propensity for local recurrence (16).…”
Section: Discussionsupporting
confidence: 83%
“…From a histological point of view, these tumours may be, or appear to be, biphasic because they are able to envelop the bronchiolar epithelium [4,5], as in our patient. It may be very difficult to ascertain the biological behaviour of LFTP based on histological findings, because the benign and malignant variants often share the same pathological features; i.e.…”
Section: Discussionmentioning
confidence: 86%
“…Solitary fibrous tumors are usually benign, rarely recur locally with invasion of adjacent tissues and rarely metastasize. It has been reported that a small percentage of solitary fibrous tumors of the pleura and mediastinum have aggressive features such as tumor necrosis and large tumor size, as well as hypercellularity, high mitotic count (Ø4 per 10 HPF) and cellular pleomorphism (Witkin & Rosai 1989;England et al 1989;Dalton et al 1979). Solitary fibrous tumors with these aggressive features may manifest with invasion of adjacent tissue, recurrence or distant metastases (England et al 1989).…”
Section: Discussionmentioning
confidence: 99%